Multidimensional perovskites : a mixed cation approach towards ambient stable and tunable perovskite photovoltaics - Koh, Teck Ming (2020)
Although halide perovskites are able to deliver high power conversion efficiencies, their ambient stability still remains an obstacle for commercialization. Thus, promoting the ambient stability of perovskites has become a key research focus. In this review, we highlight the sources of instability in conventional 3 D perovskites, including water intercalation, ion migration, and thermal decomposition. Recently, the multidimensional perovskites approach has become one of the most promising strategies to enhance the stability of perovskites. As compared to pure 2 D perovskites, multidimensional perovskites typically possess more ideal band gaps, better charge transport, and lower exciton binding energy, which are essential for photovoltaic applications. The larger organic cations in multidimensional perovskites could also be more chemically stable at higher temperatures than the commonly used methylammonium cation. By combining 3 D and 2 D perovskites to form multidimensional perovskites, halide perovskite photovoltaics can attain both high efficiency and increased stability.